Trigona sp. Propolis Ethanolic Extract Decreased Chloramphenicol-induced Serum Glutamic Oxaloacetic Transaminase and Alkaline Phosphatase Levels of Rats (Rattus novergicus) - Chanif Mahdi; Anna Zukiaturrahmah; Dyah Ayu Oktavianie Ardhiana Pratama; Putranty Widha Nugraheni (Indonesian Journal of Cancer Chemoprevention, 2018)
Liver has an important role in detoxification of toxins such as xenobiotic which could interfere the function of liver. Chloramphenicol is an antibiotic widely used,despite of its toxicity potentials. The enhancement of free radicals in the body could suppress antioxidant activity. Propolis of Trigona sp. has been known to contain very high amount of antioxidants. The enhanced serum glutamic oxaloacetic transaminase (SGOT) and alkaline phosphatase (ALP) levels in serum is used as marker of liver damage due to the increase of free radicals. The purpose of this study was to observe the effect of Trigona sp. propolis ethanolic extract on SGOT and ALP levels in rats (Rattus novergicus) pretreated by chloramphenicol to induce liver damage. Test animals used for this research were male rats aged 8-12 weeks divided into five treatment groups: negative controlgroup (normal), positive control group (induced by 400 mg/kgBW chloramphenicol), first therapy group, second therapy group, third therapy group induced by chloramphenicol with and propolis extract with the dose of 8 mg, 16 mg, and 24 mg, respectively. Chloramphenicol was injected subcutaneously for 14 days, whereas propolis extract were administered orally for 21 days. The level of SGOT and ALP was determined using spectophotometry. The results showed that propolis extract could reduce levels of SGOT and ALP. Dose of 24 mg/kg was the effective dose to decrease levels of SGOT and ALP significantly (p<0.01). Hence, it may be concluded that the ethanol extract of propolis could be used as herbal therapy in rats model of liver damage.Keywords : ALP, liver, chloramphenicol, propolis, SGOT